2022
DOI: 10.3390/healthcare10091619
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of the Essential Health and Nutrition Service Delivery in the Context of COVID-19 in Bangladesh: The Perspective of Divisional Directors

Abstract: Bangladesh suffered disruptions in the utilization of essential health and nutrition services (EHNS) during the COVID-19 pandemic. The magnitude of the pandemic has been documented, but little is known from the perspectives of health administrators. A rapid qualitative assessment of division-level capacity identified successes and bottlenecks in providing EHNS- and COVID-19-related services during the first months of the pandemic in Bangladesh. Semi-structured interviews were held with the Health and Family Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Notably, not all communities experienced reductions in ANC visits: A study in Nampula Province, Mozambique noted no disruptions and an actual increase in ANC visits, comparing data 2 years before COVID lockdowns to July 2021 (Lydon et al, 2022 ). Telehealth and mobilisation of community health workers were important interventions that improved education and outreach for COVID‐19 across geographically diverse regions of Bangladesh, but they were not optimised to ensure the continuity of essential health and nutrition services (Gaitán‐Rossi et al, 2022 ). In Kenya, national guidelines on Reproductive, Maternal, Newborn and Family Planning were published within 1 month of the first COVID‐19 case in the county Plotkin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, not all communities experienced reductions in ANC visits: A study in Nampula Province, Mozambique noted no disruptions and an actual increase in ANC visits, comparing data 2 years before COVID lockdowns to July 2021 (Lydon et al, 2022 ). Telehealth and mobilisation of community health workers were important interventions that improved education and outreach for COVID‐19 across geographically diverse regions of Bangladesh, but they were not optimised to ensure the continuity of essential health and nutrition services (Gaitán‐Rossi et al, 2022 ). In Kenya, national guidelines on Reproductive, Maternal, Newborn and Family Planning were published within 1 month of the first COVID‐19 case in the county Plotkin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This expansion did not entail additional staff, so it reduced its capacity to provide their regular services. Prior research on emergency response has shown that institutional design can hamper rapid responses (13). However, the VDS were able to quickly adapt their services as they moved along a changing crisis and managed to keep offering their regular services while adding those that were most needed in different stages of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has disrupted health systems worldwide including basic services unrelated with the pandemic (12,13). Hospital conversion has been a challenge for health facilities aiming to provide health care in safe conditions (14).…”
Section: Introductionmentioning
confidence: 99%
“…Family planning use decreased by 23% during the pandemic compared to the pre-pandemic level, and the use of oral contraceptives drastically dropped from 62 to 24% during the same period [ 18 ]. Several recent studies have recommended taking on sufficient family planning workers to restore full door-to-door services [ 17 , 18 ]. However, the interplay of such policies with patriarchal structures fails to challenge the structures that inhibit women from exercising their reproductive rights in full.…”
Section: Outreach and Gender In Family Planning Programs In Bangladeshmentioning
confidence: 99%
“…The net result has often been a simple shift in dependencies—from one on the family group to one that now includes fieldworkers as advocates, information sources, and bridges to the outside world. Yet this model is called upon in the post-Covid world to reinvigorate the family planning agenda [ 17 ], even though COVID-19 exposed the inability of the patriarchal structures to negotiate any change that would lead to a dramatic drop in contraceptive rates [ 17 , 18 ]. There is still much work to do to change the fundamental power relations in which women are embedded.…”
Section: Introductionmentioning
confidence: 99%